2001
DOI: 10.3758/bf03192816
|View full text |Cite
|
Sign up to set email alerts
|

Rats don’t always respond faster for more food: The paradoxical incentive effect

Abstract: Rats' leverpressing was reinforced on variable-ratio (VR) schedules. As ratio values increased, response rates initially increased with them, then eventually decreased. In Experiment 1, rates were uniformly higher with one-pellet reinforcers than with two-pellet reinforcers-the paradoxical incentive effect. Killeen's (1994) mathematical principles of reinforcement (MPR) described the data quantitatively but failed to predict the advantage for the one-pellet condition. In Experiment 2, rats receivedone-, two-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
47
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 51 publications
10
47
0
1
Order By: Relevance
“…Running rate was calculated by dividing the number of responses by the 'run-time' (i.e. the time taken to complete the ratio, excluding the postreinforcement pause: Bizo et al, 2001). The data were analysed as described above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Running rate was calculated by dividing the number of responses by the 'run-time' (i.e. the time taken to complete the ratio, excluding the postreinforcement pause: Bizo et al, 2001). The data were analysed as described above.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of the effect of reinforcer size on progressive-ratio schedule performance (Rickard et al, 2009) revealed that while Equation 1 provided a good description of overall response rate, its fit to the 'running' response rate (response rate calculated after exclusion of the post-reinforcement pause: Bizo et al, 2001) was less satisfactory. Running response rate was, however, well described by the logistic function:…”
Section: Introductionmentioning
confidence: 99%
“…Running rate was calculated by dividing the number of responses by the "run-time" (i.e. the time taken to complete the ratio, excluding the post-reinforcement pause: Bizo et al 2001). The data were analysed as described Because the number of ratios completed within a session under a progressiveratio schedule differs among individual subjects, analyses of variance of the raw response rates included only those ratios that were completed by at least 75% of the rats in each group under each treatment condition (ratios up to and including 62 in the case of the haloperidol series and up to and including 118 in the case of all other drugs), missing values being filled using the value obtained in the highest ratio completed by the subject in question (Rickard et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It can happen because the third and fourth reinforcers (or the third and fourth seconds of the same reinforcing event) are more remote from the target response than are the first and second events (or seconds; Killeen, 1985). It can also happen because extended reinforcement epochs block the reinforcement of responses by the subsequent reinforcers (Bizo, Kettle, & Killeen, 2001). These are behavioral mechanisms that can be tested with behavioral arrangements.…”
Section: An Economic Modelmentioning
confidence: 99%